2022
DOI: 10.1177/03009858221082228
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial pneumonia and diffuse alveolar damage in domestic animals

Abstract: Classification of pneumonia in animals has been controversial, and the most problematic pattern is interstitial pneumonia. This is true from the gross and histologic perspectives, and also from a mechanistic point of view. Multiple infectious and noninfectious diseases are associated with interstitial pneumonia, all of them converging in the release of inflammatory mediators that generate local damage and attract inflammatory cells that inevitably trigger a second wave of damage. Diffuse alveolar damage is one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 182 publications
1
11
0
Order By: Relevance
“…[47][48][49][50] DAD represents injury to type I pneumocytes or endothelial cells in the alveolar septa and is characterized by inflammation in the alveolus and alveolar septa and type II pneumocyte hyperplasia. [51][52][53] Although we observed no differences in composite lung pathology between lean and obese infected groups (Figure 3A,C), we did identify type II pneumocyte hyperplasia and inflammation of alveoli and alveolar septa in C57BL/6 N and C3H/ HeJ (Figure 4) mice, consistent with DAD, confirming the validity of our MHV-1 infection models for studying COVID-19 pathogenesis.…”
Section: Discussionsupporting
confidence: 70%
“…[47][48][49][50] DAD represents injury to type I pneumocytes or endothelial cells in the alveolar septa and is characterized by inflammation in the alveolus and alveolar septa and type II pneumocyte hyperplasia. [51][52][53] Although we observed no differences in composite lung pathology between lean and obese infected groups (Figure 3A,C), we did identify type II pneumocyte hyperplasia and inflammation of alveoli and alveolar septa in C57BL/6 N and C3H/ HeJ (Figure 4) mice, consistent with DAD, confirming the validity of our MHV-1 infection models for studying COVID-19 pathogenesis.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, the fibrosis could be promoted by the prolonged presence of an unfavorably polarized inflammatory response. In addition to macrophages, AT2 cells can promote a pro-fibrotic microenvironment by activating local fibroblasts to become myofibroblasts via paracrine signaling, as demonstrated in vitro 45,61,62 . This process was initiated by an induction of an EMT process in the AT2 cells 53,62 .…”
Section: Discussionmentioning
confidence: 94%
“…7 L ). Finally, we investigated the expression of genes involved in angiogenesis, since this process is upregulated in late phases of DAD, in the context of fibrosis 45 . A small number of cells within the AT1/ADI cluster at 5 dpi and a higher number of cells within the AT1/ADI and ADI clusters at 14 dpi revealed high positive scores for angiogenesis hallmark genes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining pneumonic patterns presented percentages less than 1% (n ≤ 2). Two individuals presented interstitial lung disease (diffuse alveolar damage) in exudative stage; this nding is attributed to ventilation-induced lung injury in the euthanasia procedure 11 . In the study, no evidence of bronchointerstitial pneumonic patterns was found.…”
Section: Lung Parenchymamentioning
confidence: 95%